The behaviour change wheel: A new method for characterising and design ing behaviour change interventions - Michie, Susan; Stralen, Maartje M; West, Robert (Implementation Science : IS, 2011)
Background Improving the design and implementation of evidence-based p ractice depends on successful behaviour change interventions. This req uires an appropriate method for characterising interventions and linki ng them to an analysis of the targeted behaviour. There exists a pleth ora of frameworks of behaviour change interventions, but it is not cle ar how well they serve this purpose. This paper evaluates these framew orks, and develops and evaluates a new framework aimed at overcoming t heir limitations. Methods A systematic search of electronic databases and consultation with behaviour change experts were used to identify f rameworks of behaviour change interventions. These were evaluated acco rding to three criteria: comprehensiveness, coherence, and a clear lin k to an overarching model of behaviour. A new framework was developed to meet these criteria. The reliability with which it could be applied was examined in two domains of behaviour change: tobacco control and obesity. Results Nineteen frameworks were identified covering nine int ervention functions and seven policy categories that could enable thos e interventions. None of the frameworks reviewed covered the full rang e of intervention functions or policies, and only a minority met the c riteria of coherence or linkage to a model of behaviour. At the centre of a proposed new framework is a 'behaviour system' involving three e ssential conditions: capability, opportunity, and motivation (what we term the 'COM-B system'). This forms the hub of a 'behaviour change wh eel' (BCW) around which are positioned the nine intervention functions aimed at addressing deficits in one or more of these conditions; arou nd this are placed seven categories of policy that could enable those interventions to occur. The BCW was used reliably to characterise inte rventions within the English Department of Health's 2010 tobacco contr ol strategy and the National Institute of Health and Clinical Excellen ce's guidance on reducing obesity. Conclusions Interventions and polic ies to change behaviour can be usefully characterised by means of a BC W comprising: a 'behaviour system' at the hub, encircled by interventi on functions and then by policy categories. Research is needed to esta blish how far the BCW can lead to more efficient design of effective i nterventions.